Neuroprotective and anti‐inflammatory effects of curcumin in Alzheimer's disease: Targeting neuroinflammation strategies - Azzini, Elena; Peña‐Corona, Sheila I.; Hernández‐Parra, Héctor; Chandran, Deepak; Saleena, Lejaniya Abdul Kalam; Sawikr, Yousef; Peluso, Ilaria; Dhumal, Sangram; Kumar, Manoj; Leyva‐Gómez, Gerardo; Martorell, Miquel; Sharifi‐Rad, Javad; et al. (Phytotherapy research, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by the accumulation of amyloid‐beta plaques and neurofibrillary tangles, leading to neuronal loss. Curcumin, a polyphenolic compound derived from Curcuma longa , has shown potential neuroprotective effects due to its anti‐inflammatory and antioxidant properties. This review aims to synthesize current preclinical data on the anti‐neuroinflammatory mechanisms of curcumin in the context of AD, addressing its pharmacokinetics, bioavailability, and potential as a therapeutic adjunct. An exhaustive literature search was conducted, focusing on recent studies within the last 10 years related to curcumin's impact on neuroinflammation and its neuroprotective role in AD. The review methodology included sourcing articles from specialized databases using specific medical subject headings terms to ensure precision and relevance. Curcumin demonstrates significant neuroprotective properties by modulating neuroinflammatory pathways, scavenging reactive oxygen species, and inhibiting the production of pro‐inflammatory cytokines. Despite its potential, challenges remain regarding its limited bioavailability and the scarcity of comprehensive human clinical trials. Curcumin emerges as a promising therapeutic adjunct in AD due to its multimodal neuroprotective benefits. However, further research is required to overcome challenges related to bioavailability and to establish effective dosing regimens in human subjects. Developing novel delivery systems and formulations may enhance curcumin's therapeutic potential in AD treatment.